BENTENG VAN DEN BOSCH, NGAWI: TEMUAN ARTEFAKTUAL SEBAGAI CERMINAN ALAT-ALAT KEBUTUHAN SEHARI-HARI - Chawari, Muhammad (Berkala Arkeologi, 2016)
Research in Fort Van den Bosch in Ngawi, East Java Province brings about data on aspects of the buildings and artifacts that accompany it. Regarding the artifacts a number of fragments of pottery, metal, ceramics, glass, animal bones, and shells have been found. They were objects of everyday appliances, except for bones and shells. Those artefacts could show the activities of the fort’s inhabitants in the past.